Scale, diversity, and determinants of labour migration in Europe - Anzelika Zaiceva; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2008)
While global migration is increasing, internal EU migration flows have remained low. This paper contributes to a better understanding of the determinants and scale of European migration. It surveys previous historical experiences and empirical findings including the recent Eastern enlargements. The determinants of migration before and after the 2004 enlargement and in the EU15 and EU10 countries are analysed using individual data on migration intentions. In addition, perceptions about the size of migration after the enlargement are studied. The potential emigrant from both old and new EU member states tends to be young, better educated and to live in larger cities. People from the EU10 with children are less likely to move after enlargement in comparison to those without family. There exists a correlation between individual perceptions about the scale of migration and actual flows. Better educated and left-oriented individuals in the EU15 are less likely to perceive these flows as important.
urn:nbn:de:101:1-2008072348
Keywords: F22; 330; Migration; EU Eastern enlargement; migration intentions; determinants of labour migration; Internationale Wanderung; Internationale Arbeitsmobilität; EU-Erweiterung; EU-Staaten